INITIAL DEVELOPMENT OF CLADODE GIANT SWEET CLONE AS A FUNCTION OF WATER AND SALINE STRESS - LUCENA, Leandro Ricardo Rodrigues de; COSTA, Álefe Chagas de Lima; OLIVEIRA, Antonio Dennys Melo de; LEITE, Maurício Luiz de Mello Vieira (Brazilian Journal of Biometrics, 2021)
Forage plants are considered one of the main factors for the development of livestock worldwide, for presenting high potential for phytomass production, drought tolerance, high energy value, large water reserve and easy propagation. Forage cactus stands out for its tolerance to water deficit. Aimed to evaluate the initial performance of the morphometric characteristics of Giant Sweet clone (N. cochenillifera) submitted to water and saline stresses using response surface analysis. Design used was completely randomized in a 4x4 factorial scheme, composed of four levels of water replacement, based on crop evapotranspiration (ETc): (25%.ETc, 50%.ETc, 75%.ETc and 100%.ETc) and four levels of water salinity (0, 2, 4 and 8 dS/m), with four repetitions totalling 64 experimental units. The following morphometric characteristics were evaluated: plant height, length, width, thickness, number of cladodes and area of cladodes. Eight evaluations were realized during the experimental period. Response surface analysis was used to evaluate the morphometric characteristics of the cladodes. Best water levels were between 55%.ETc and 65%.ETc and saline levels between 3.5 and 5 dS/m, maximizing the morphometric characteristics of Giant Sweet clone.